Surgical site infection in spinal surgery: a comparative study between 2-octyl-cyanoacrylate and staples for wound closure - Ando, Muneharu (Springer Berlin Heidelberg, 2014)
BACKGROUND: Surgical site infection (SSI) after spinal surgery is a devastating complication. Various methods of skin closure are used in spinal surgery, but the optimal skin-closure method remains unclear. A recent report recommended against the use of metal staples for skin closure in orthopedic surgery. 2-Octyl-cyanoacrylate (Dermabond; Ethicon, NJ, USA) has been widely applied for wound closure in various surgeries. In this cohort study, we assessed the rate of SSI in spinal surgery using metal staples and 2-octyl-cyanoacrylate for wound closure. METHODS: This study enrolled 609 consecutive patients undergoing spinal surgery in our hospital. From April 2007 to March 2010 surgical wounds were closed with metal staples (group 1, n = 294). From April 2010 to February 2012 skin closure was performed using 2-octyl-cyanoacrylate (group 2, n = 315). We assessed the rate of SSI using these two different methods of wound closure. Prospective study of the time and cost evaluation of wound closure was performed between two groups. RESULTS: Patients in the 2-octyl-cyanoacrylate group had more risk factors for SSI than those in the metal-staple group. Nonetheless, eight patients in the metal-staple group compared with none in the 2-octyl-cyanoacrylate group acquired SSIs (p < 0.01). The closure of the wound in length of 10 cm with 2-octyl-cyanoacrylate could save 28 s and $13.5. CONCLUSIONS: This study reveals that in spinal surgery, wound closure using 2-octyl-cyanoacrylate was associated with a lower rate of SSI than wound closure with staples. Moreover, the use of 2-octyl-cyanoacrylate has a more time saving effect and cost-effectiveness than the use of staples in wound closure of 10 cm in length.